Substrates for in vitro adventitious root induction and development on two apple rootstocks - Hoffmann, Alexandre; Pasqual, Moacir; Chalfun, Nilton Nagib Jorge; Vieira, Sílvia Serra Negra (Pesquisa Agropecuaria Brasileira, 2001)
This work was carried out to study the effect of vermiculite and Plantmax as alternative substrates for agar during both in vitro rooting induction and adventitious root development on 'Marubakaido' and 'M-26' apple (Malus domestica Borkh.) rootstocks. Apical shoots previously maintained in vitro were used. This experiment was divided in two phases. On phase 1, treatments were constituted by three substrates for rooting induction: agar, Plantmax + agar and vermiculite + agar, with MS/2 medium with vitamins, glicyne, myinositol, sucrose and indolebutyric acid (IBA). After seven days in this medium, shoots were transferred to medium with agar (7 g L-1) and without IBA. On phase 2, three substrates were assayed for adventitious roots development (agar, Plantmax and vermiculite, wettish with MS medium) after a seven-day induction time on a medium with agar (7 g L-1). The effect of treatments was evaluated both in vitro and during environment acclimatization. The use of agar during rooting induction and agar or Plantmax, during adventitious root development provided the best results for 'Marubakaido' and 'M-26' plantlets, on in vitro rooting and during acclimatization.